Expansão da área agrícola e produtividade das culturas no Brasil: testando hipóteses da legislação californiana de biocombustíveis - Daubermann, Elaine Correa (2014)
We investigate the hypothesis that the conversion of forest and pasture land to cropland in Brazil decreases yields by 50%. Such hypothesis is being used by the California Air Resource Board to estimate the greenhouse gas emissions from indirect land use changes due to the expansion of biofuels production. We formulate several econometric models to test such hypothesis. The results from the majority of the models indicate that yields do not decrease under the expansion of cropland area in the country, or the decrease in yields is very small. Therefore, our results indicate the need for revising and correcting the parameters in the Californian low carbon emissions policy.